Backsliding and reversal: The J-Curve revisited - Rachael Calleja; David Carment; Mark Haichin; Peter Tikuisis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Ian Bremmer published a treatise on the stability of states built on the notion that states fall along a curve resembling a slanted "J" when plotting their stability against openness. States in the turnover process are considered unstable, and are at risk of either reversing to a closed and stable system or even collapsing. Our paper shifts the J curve's associated conditions to a model to more accurately specify the causes of reversal in which crises of instability and backsliding occur. We define stability as a function of two state dimensions: authority and capacity, and apply the remaining state dimension of legitimacy as a proxy for openness. We find that transitions can reverse, oscillate, or simply stall, which are exemplified in the different types of states we categorize. The paper concludes with implications for policy and the application of the model to conflict prediction.
Keywords: C52; C55; 330; democracy; backsliding; fragile states; instability; hybrid states; forecasting